Cash Holding, Leverage, Political Connections, and Earnings Quality:The Moderating Role of Corporate Social Responsibility - Rashidi Amin; Amrie Firmansyah (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
This study aims to examine the influence of cash holding, leverage and political connections (CSR) on earnings quality. In addition, the moderating role of corporate social responsibility in the relationship between the variables also examined. Data were collected from financial statements and sustainability reports of Indonesian manufacturing companies, listed on the Indonesia Stock Exchange (IDX). Data were derived from the Indonesian stock exchange website and the company's official website. Using purposive sampling method, 424 firm-year observations between 2017 and 2020 were analyzed using multiple linear regression analysis for panel data. The results of this study reveal that cash holding is negatively associated with earnings quality, while leverage is positively associated with earnings quality, and political connections are not associated with earnings quality. Furthermore, CSR does not have a role in weakening the negative effect of cash holding, leverage and political connections on earnings quality.